Plasma isotopic changeover experiments in JET under carbon and ITER-like wall conditions. (30th March 2015) - Loarer, T.; Brezinsek, S.; Philipps, V.; Romanelli-Gruenhagen, S.; Alves, D.; Carvalho, I.; Felton, R.; Douai, D.; Esser, H.G.; Frigione, D.; Smith, R.; Stamp, M.F.; et al.
Abstract: In JET-ILW isotopic plasma wall changeover experiments have been carried out to determine the amount of particles accessible by changing the plasma from H to D and from D to H. The gas balance analysis integrated over the experimental sessions show that the total amount of H or D removed from the wall is in the range of (1–3) × 10 22 D. For both changeover experiments, the respective plasma isotopic ratio behaviour is exactly the same as a function of the pulse number. After only 80 s of plasma (4 pulses), the plasma isotopic ratio is lower than 10%, below 4.5% after 13 pulses and then saturates around ∼2–3%. In these conditions, the removal efficiency through plasma operation becomes very poor. The saturation of the plasma isotopic ratio in the range of 10% is also observed for the JET-C configuration although the amount of tritium retained in the vessel after the DT pulses was more than one order of magnitude compared to the retention observed with the JET-ILW. This demonstrates that the amount of particle recovery through plasma changeover is independent from the long term retention. Since this long term reservoir results from codeposition, these experiments suggest that there is a limited access to these codeposited particles by plasma isotopic changeover. Finally, in ITER, change over from D/T to H at the end of the discharge for possibly reducing the long term retention does not appear as a good strategy.